Stereotactic Radiosurgery for Trigeminal Neuralgia in Patients With Multiple Sclerosis: A Multicenter Study. Issue 2 (23rd April 2018) - Xu, Zhiyuan; Mathieu, David; Heroux, France; Abbassy, Mahmoud; Barnett, Gene; Mohammadi, Alireza M; Kano, Hideyuki; Caruso, James; Shih, Han-Hsun; Grills, Inga S; Lee, Kuei; Krishnan, Sandeep; et al.
Abstract: BACKGROUND: Facial pain response (PR) to various surgical interventions in patients with multiple sclerosis (MS)-related trigeminal neuralgia (TN) is much less optimal. No large patient series regarding stereotactic radiosurgery (SRS) has been published. OBJECTIVE: To evaluate the clinical outcomes of MS-related TN treated with SRS. METHODS: This is a retrospective cohort study. A total of 263 patients contributed by 9 member tertiary referral Gamma Knife centers (2 in Canada and 7 in USA) of the International Gamma Knife Research Consortium (IGKRF) constituted this study. RESULTS: The median latency period of PR after SRS was 1 mo. Reasonable pain control (Barrow Neurological Institute [BNI] Pain Scores I-IIIb) was achieved in 232 patients (88.2%). The median maintenance period from SRS was 14.1 months (range, 10 days to 10 years). The actuarial reasonable pain control maintenance rates at 1 yr, 2 yr, and 4 yr were 54%, 35%, and 24%, respectively. There was a correlation between the status of achieving BNI-I and the maintenance of facial pain recurrence-free rate. The median recurrence-free rate was 36 mo and 12.2 mo in patients achieving BNI-I and BNI > I, respectively ( P = .046). Among 210 patients with known status of post-SRS complications, the new-onset of facial numbness (BNI-I or II) after SRS occurred in 21 patients (10%). CONCLUSION: In this largest series SRS offers a reasonable benefit to risk profile for patients who have exhausted medical management. More favorable initial response to SRS may predict a long-lasting pain control.